2008
DOI: 10.1007/s11064-007-9583-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Diabetes on Glycogen Metabolism in Rat Retina

Abstract: Glucose is the main fuel for energy metabolism in retina. The regulatory mechanisms that maintain glucose homeostasis in retina could include hormonal action. Retinopathy is one of the chemical manifestations of long-standing diabetes mellitus. In order to better understand the effect of hyperglycemia in retina, we studied glycogen content as well as glycogen synthase and phosphorylase activities in both normal and streptozotocin-induced diabetic rat retina and compared them with other tissues. Glycogen levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 51 publications
3
15
0
Order By: Relevance
“…Animal models of diabetes characterised by insulin deficiency and chronic hyperglycaemia show unaltered glucose transport at the blood-brain-barrier [98], thus leading to high brain glucose concentration at hyperglycaemia. In chronic, sustained hyperglycaemia, the rodent brain does not display evident alteration of brain glycogen levels [195][196][197][198]. On the other hand, it is not clear whether insulin regulates whole brain glycogen deposition.…”
Section: Hypoglycaemia and Hypoglycaemia Unawarenessmentioning
confidence: 99%
“…Animal models of diabetes characterised by insulin deficiency and chronic hyperglycaemia show unaltered glucose transport at the blood-brain-barrier [98], thus leading to high brain glucose concentration at hyperglycaemia. In chronic, sustained hyperglycaemia, the rodent brain does not display evident alteration of brain glycogen levels [195][196][197][198]. On the other hand, it is not clear whether insulin regulates whole brain glycogen deposition.…”
Section: Hypoglycaemia and Hypoglycaemia Unawarenessmentioning
confidence: 99%
“…Previous studies have shown that although GS activity increases in several tissues in diabetic animals, including brain, only retina showed an increase in glycogen content. 22 Glycogen metabolism in the retina may differ fundamentally to the rest of the CNS, although gross glycogen storage in the perikarya of hypothalamic neurons has been demonstrated in long-term diabetic rats, and was associated with cell-specific neurodegeneration. 32 In the current study, the pattern of nuclear sequestration of pGS was seen to change significantly in the diabetic retina.…”
Section: Glycogen Storage In Diabetic Retinamentioning
confidence: 99%
“…13 Although primary neurodegeneration and functional hypoxia represent features of early diabetic retinopathy, [14][15][16][17][18][19] increased glycogen synthesis in the diabetic retina, although the cellular distribution of the polysaccharide has not been addressed. [20][21][22] It is therefore important to document the distribution of glycogen in retinal neurons and to consider the possible roles of this important glucose storage molecule in the context of diabetic retinopathy.…”
mentioning
confidence: 99%
“…An in vitro study found the activity of hexokinase (engaging glucose in glycolysis) reduced whereas those of glycogen phosphorylase and synthase increased in cortical slices of diabetic rats, suggesting glycogen to be a more important fuel than glucose for oxidation in this case [52]. Increased activity of glycogen synthase has also been found in the cortex of type 1 diabetic rats, however without any concentration alterations [53]. These findings indicate that perturbed glycogen metabolism is one key feature of the diabetic brain, not necessarily accompanied by modifications of net glycogen content.…”
Section: Brain Glycogen and Energetic Dysfunction In Diseasementioning
confidence: 99%
“…For instance, glycogen pools across the brain have been shown to be differently affected by diabetes, e.g. reduced glycogen levels were found in the cerebellum of type 2 obese diabetic rats [54], and increased glycogen content was reported in the retina of type 1 diabetic rats [53]. Altered brain glycogen metabolism in diabetes may play an important role in hypoglycemia unawareness, a situation where the blood glucose threshold to elicit a counter-regulatory response is reduced [29,47,55e58].…”
Section: Brain Glycogen and Energetic Dysfunction In Diseasementioning
confidence: 99%